EFFECT LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE ON PERFORMANCE WITH WORK MOTIVATION AS INTERVENING VARIABLE - Siti Juhaeni; Herdiana Eta Prananti; CSP Wekadigunawan; Hasyim Hasyim (Kesatuan Press, 2023)
With work motivation as an auxiliary variable, this study seeks to ascertain the impact of leadership style and organizational culture on the performance of specialist doctors. This study is a cross sectional study with 65 specialist doctors as respondents. Collecting data for the four variables using a linkert scale of 1-5 points and as a test tool descriptive statistical analysis is used with a three box method approach which is divided into three scale ranges, namely H (High), M (Medium), and L (Low). The results of the analysis of sub-structure 1 and the probability value simultaneously and partially indicating that the leadership style, organizational culture, and work motivation simultaneously and partially have a positive and substantial impact on performance. Sub structure 2 and the comparison of probability values simultaneously and partially shows that simultaneously and partially leadership style and organizational culture have an effect positive and significant effect on work motivation. The equation of path of total influence shows that job motivation influences leadership style and organizational culture in a way that enhances the performance of specialist doctors.